Direct Measurement of Blast Pressure in Near Field with Lead Plate Blast Pressure Meter - Ko, Y.; Jang, Hyong Doo; Yang, H. (Korean Society for Rock Mechanics, 2012)
Deformation of Lead plate blast pressure meter were measured after they were exposed to surface blasting. Blasting pressure was determined by comparing the data with calibration graph which was drawn from the laboratory experiments with gas gun of Hopkinson bar tester. The results were compared with calculated values from the equations of CONWEP (Conventional Weapons Effects Program) and DDESB (Department of Defence Explosives Safety Board). Measured values were lower than calculated values in near field. Gradual decaying tendency of the pressure was observed. It means that estimated blasting pressure of very near field with theoretical equations can be uncertain.